PSII-18 The effects of fish oil supplementation on markers of inflammation and skeletal muscle and adipose growth in pigs. (8th October 2021) - Okamoto, Lillian L; Reichhardt, Caleb C; Lopez, Sierra; Alberto, Anthony F; Briggs, Reganne K; Smith, Laura A; Batistel, Fernanda; Thornton, Kara J
Abstract: Omega-3 fatty acids have immunomodulatory and anti-inflammatory effects. The objective of this project was to determine the effects of fish oil, a source of omega-3 fatty acids, on genes involved in inflammation and growth of skeletal muscle tissue after an LPS challenge. Male Landrace-New Hampshire weaned piglets (BW 8.21±0.83 kg) were used in a randomized complete block design and assigned to two treatments: 1) basal diet (n=7) and 2) basal diet plus 3% fish oil added (n = 7). Treatments were fed for 35 d. On d 34, an LPS challenge was performed and 24 h later, piglets were euthanized and skeletal muscle samples were collected from the longissimus lumborum and biceps femoris. Total mRNA was isolated and markers of inflammation [cyclophilin (Cyclo), nuclear factor kappa beta subunit-1 (NF-kB), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6)], skeletal muscle growth [paired box transcription factor-7 (Pax7), myogenic factor-5 (Myf5), myoblast determination factor-1 (MyoD), myogenin (MyoG)] and adipose growth (peroxisome proliferator activated receptor (PPARy), leptin, and adiponectin) were analyzed. Cyclophilin abundance was increased (P = 0.03) in fish-oil piglets compared to control piglets. Other markers of inflammation (TNF-α, IL-6, NF-kB) were not affected (P > 0.05) by fish-oil supplementation. Abundance of Myf5 was lower (P = 0.03) in fish oil piglets than control piglets. Other myogenic regulatory factors (Pax7, MyoD, MyoG) were not (P > 0.05) altered by treatment. Abundance of PPARy, leptin or adiponectin was not affected (P > 0.05) by fish-oil supplementation. Muscle location influenced (P < 0.01) abundance of leptin and adiponectin, with abundance being higher in the biceps femoris than in the longissimus lumborum. No other genes analyzed were impacted by muscle location (P > 0.05). Our findings suggest that supplementation of omega-3 fatty acids via fish-oil may affect the inflammatory response and skeletal muscle growth. Further research is needed to evaluate the impact of these results on animal production.